Ideologia pracy w świadomości przemysłowej klasy robotniczej - Haber, Lesław H. (Wydział Prawa i Administracji UAM, 1988)
Treating ideology of work as a symptom of positive attitude of an individual towards the work he/she performs, the symptom reflected both in the philosophy of work as well as in acting, the author considers it i two planes: genetic and structural-functional. Genetic analysis allows the author to show actual causes of revaluing the ideology of work, with the attention focused on official version of that ideology. Structural-functional planes are analysed through the results of sociological research conducted among 2283 metal industry workers from Cracow, Warsaw and Katowice provinces. The research allowed to single out three distinct forms of ideology functioning in the working class consciouseness: official, catholic and pragmatic, with the last one prevailing over the remaining two. Further analysis is devoted to interdependencies existing between the form of ideology, the work environment, situations occuring at a workplace and selected features of the social status.
Ideology of work in the consciousness of the industrial working class